THE IMPACT OF WORK ENVIRONMENT, COMMUNICATION AND LEADERSHIP ON PERFORMANCE OF EMPLOYEES IN TARAKAN CITY EDUCATION OFFICE - Pendi Tandi Bua; Theodorus Kristianto; Achmad Daengs GS (Universitas 17 Agustus 1945 Surabaya, 2020)
This study aims to examine and analyze the influence of the working environment of communication and leadership to wards the performance of employees in the education department of Tarakan city. Data collection was done by distributing questionnaires and carried out on 48 people who were samples in this research. The sample technique used is random and data testing techniques used in this research include validity test with factor analysis, reliability test with Alpha Cronbach. Multiple linear regression analysis. The results of the t test showed that the partial variable of the working environment has positive and significant effect on the performance of employees in the education departmet of tarakan city, so the hypothesis in the proposed proved true (T-test = 2,731 > T-table 2.012) .T test results showed that the communication variables have a positive and significant impac on the performance of employees in the education departmet of tarakan city, so the hypothesis in the proposed proved true (T-test = 3,339 > T-table 2.012). T test results showed that the Leadership to word variables have a positive and significant impac on the performance of employees in the education departmet of tarakan city, so the hypothesis in the proposed proved true (T-test = 2,846 > T-table 2.012) The results of f test showed that the working enviroment of comunication and leadership positiv effect and significant to the performance of employees in the education departmet of tarakan city , so the hypothesis in the proposed proved true (F-test = 81,195 > F-tabel 2,82).